Beer and Allergens - Frank Vriesekoop (Beverages, 2021)
Food allergies are an important global health concern, with many countries following the World Health Organisation’s guidelines with regards to due labelling of foods and, as such, providing forewarning about the presence of potential allergens to potential consumers. While for some produce, the link to specific allergens might be very clear to most consumers, this is not the case for all produce. People with specific food-related allergies usually know what to look out for, but occasionally, unexpected allergens are present in trusted produce. Beer is known to most to contain barley, which will contain gluten-like proteins that can cause allergic reactions in some people. Similarly, beer might contain sulphites and other potential allergens traditionally associated with beers. This review aims to examine a wide range of allergens that have entered the beer production process in recent years. As a result, examples of beers that contain one or more of the 14 EU-UK listed allergens are described, different allergen regulations in different countries are emphasised and their impact explained, and a number of case studies involving allergic reactions following exposure to and the ingestion of beer are highlighted.